2012
DOI: 10.1021/ac302256d
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal Supercharging in Mass Spectrometry and Tandem Mass Spectrometry of Native Proteins

Abstract: Electrothermal supercharging of protein ions formed by electrospray ionization from buffered aqueous solutions results in significant increases to both the maximum and average charge states compared to native mass spectrometry in which ions are formed from the same solutions but with lower spray potentials. For eight of the nine proteins investigated, the maximum charge states of protonated ions formed from native solutions with electrothermal supercharging is greater than those obtained from conventional dena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 72 publications
(167 reference statements)
3
74
0
Order By: Relevance
“…As a result, the stainless steel emitter could not be used in negative ESI. Cassou et al reported negative nano-ESI of water solution by using borosilicate capillary with an ESI spray potential of -0.7 kV and a 3-mm distance between the emitter and the counter electrode [53]. We were not able to achieve stable ESI with the same field strength, presumably because of the higher flow rate we used.…”
Section: On-line Sampling For Spectroscopy and Esi Msmentioning
confidence: 86%
“…As a result, the stainless steel emitter could not be used in negative ESI. Cassou et al reported negative nano-ESI of water solution by using borosilicate capillary with an ESI spray potential of -0.7 kV and a 3-mm distance between the emitter and the counter electrode [53]. We were not able to achieve stable ESI with the same field strength, presumably because of the higher flow rate we used.…”
Section: On-line Sampling For Spectroscopy and Esi Msmentioning
confidence: 86%
“…41 Cytochrome c has been well-studied by mass spectrometry not only for chemical analysis in proteomics 30,31,42,43 but also for protein conformation studies in structural biology. [44][45][46][47] ESI-MS of a given protein usually results in a charge state distribution (CSD) corresponding to multiply charged ions and the CSD shifts to higher charge states (low m/z) when the protein unfolds under extreme conditions such as an acidic or heated solution. 48 While there has been some debate concerning the use of charge states to determine the conformation of protein molecules in mass spectrometry, 45 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 folded conformations with detection of a small amount of unfolded protein.…”
Section: Vaporization Of Dried Cytochrome C From Stainless Steel and mentioning
confidence: 99%
“…Kathrin Breuker (University of Innsbruck, Innsbruck, Austria) considered the relationship between the rate of gas-phase unfolding of a protein versus the efficiency of dissociation after electron capture events, illustrating the benefits of unfolding. Evan Williams (University of California at Berkeley, CA, USA) described the use of reagents that modify the electrospray ionization process for supercharging of protein ions, and introduced electrothermal supercharging [7].…”
Section: Intact Protein Mass Spectrometry and Top-down Proteomicsmentioning
confidence: 99%